The Influence of Stress on Decision-Making: Effects of CRF and Dopamine Antagonism in the Nucleus Accumbens - Williams, Rapheal G.; Li, Kevin H.; Phillips, Paul E. M. (Frontiers in Psychiatry, 2022)
The actions of corticotropin-releasing factor (CRF) in the core of the nucleus accumbens including increasing dopamine release and inducing conditioned place preference in stress-naïve animals. However, following two-day, repeated forced swim stress (rFSS), neither of these effects are present, indicating a stress-sensitive interaction between CRF and dopamine. To ascertain the degree to which this mechanism influences integrated, reward-based decision making, we used an operant concurrent-choice task where mice could choose between two liquid receptacles containing a sucrose solution or water delivery. Following initial training, either a CRF or dopamine antagonist, α-helical CRF (9-41) and flupenthixol, respectively, or vehicle was administered intracranially to the nucleus accumbens core. Next, the animals underwent rFSS, were reintroduced to the task, and were retested. Prior to stress, mice exhibited a significant preference for sucrose over water and made more total nose pokes into the sucrose receptacle than the water receptacle throughout the session. There were no observed sex differences. Stress did not robustly affect preference metrics but did increase the number of trial omissions compared to their stress-naïve, time-matched counterparts. Interestingly, flupenthixol administration did not affect sucrose choice but increased their nosepoke preference during the inter-trial interval, increased trial omissions, and decreased the total nosepokes during the ITI. In contrast, microinjections of α-helical CRF (9-41) did not affect omissions or ITI nose pokes, but produced interactions with stress on choice metrics. These data indicate that dopamine and CRF both interact with stress to impact performance in the task but influence different behavioral aspects.